RUANG MUSIK DAN KERJA PADA BANGUNAN EX TOKO TIO TEK HONG DI PASAR BARU JAKARTA PUSAT - Williyanto, Daniel; Suteja, Mekar Sari (Jurusan Arsitektur dan Perencanaan, 2024)
Pasar Baru is a trading area in the Sawah Besar District, Central Jakarta. Established in the 19th century, it is one of Jakarta's oldest shopping centers. Initially a bustling trading hub inhabited by the Chinese and Dutch, Pasar Baru's historical buildings have now undergone functional transformations, with diminishing community recognition of their historical significance. Over time, many historic buildings in Pasar Baru have lost their identity, becoming